2020
DOI: 10.1109/jtehm.2020.2989768
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Development Environment for EEG-Driven Cognitive-Neuropsychological Research

Abstract: Background: EEG-driven research is paramount in cognitive-neuropsychological studies, as it provides a non-invasive window to the underlying neural mechanisms of cognition and behavior. A myriad collection of software and hardware frameworks has been developed to alleviate some of the technical barriers involved in EEG-driven research. Methods: we propose an integrated development environment which encompasses the entire technical ''data-collection pipeline'' of cognitive-neuropsychological research, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The review found that the use of neural networks to develop computational architectures is oriented toward the design of the networks, followed by learning algorithms to simulate different brain functions in 38.1% [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Next, the development of brain simulation software is 14.3% [ 49 , 50 , 51 ], and the development of hybrid architectures (using brain computing interfaces supported by neuromorphic processors) accounts for 14.3% [ 52 , 53 , 54 ]. The development and improvement of brain computing interfaces was 9.5% [ 55 , 56 ], as was analysis and database storage through machine learning [ 57 , 58 ].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The review found that the use of neural networks to develop computational architectures is oriented toward the design of the networks, followed by learning algorithms to simulate different brain functions in 38.1% [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Next, the development of brain simulation software is 14.3% [ 49 , 50 , 51 ], and the development of hybrid architectures (using brain computing interfaces supported by neuromorphic processors) accounts for 14.3% [ 52 , 53 , 54 ]. The development and improvement of brain computing interfaces was 9.5% [ 55 , 56 ], as was analysis and database storage through machine learning [ 57 , 58 ].…”
Section: Methods and Resultsmentioning
confidence: 99%